Repeated exposure to food and food acceptability in infants and toddlers: a systematic review. (28th March 2019) - Spill, Maureen K; Johns, Kirsten; Callahan, Emily H; Shapiro, Myra J; Wong, Yat Ping; Benjamin-Neelon, Sara E; Birch, Leann; Black, Maureen M; Cook, John T; Faith, Myles S; Mennella, Julie A; Casavale, Kellie O
ABSTRACT: Background: Repeated exposure has been found to be an effective strategy to increase acceptability of foods in older children and adults, but little is known about its effectiveness in the birth to 24-mo population. Objectives: This systematic review was conducted to examine the effects of repeated exposure to a single or multiple foods on acceptance of those or other foods among infants and toddlers. Methods: A search was conducted for peer-reviewed articles related to food acceptability, flavor, taste, and infants and toddlers in 12 databases (e.g., PubMed, Embase, Cochrane, and CINAHL) with a date range of January 1980 to July 2017. The Nutrition Evidence Library (NEL) Bias Assessment Tool was used to assess potential bias in the included studies, and the NESR grading rubric was used to grade evidence supporting the conclusion statement. Results: From the 10, 844 references obtained, 21 studies (19 controlled trials and 2 longitudinal cohort studies) published from 1980 to 2015 were included in this review. Moderate evidence indicates that tasting a single vegetable or fruit or multiple vegetable(s) or fruit(s) 1 food per day for 8–10 or more days is likely to increase acceptability of an exposed food (indicated by an increase in intake or faster rate of feeding after comparison with before the exposure period) in infants and toddlers 4–24 mo old. The effect of repeated exposure on acceptability is likely to generalize to other foods within the same food category but not foods from a different food category. Findings are based on the effects of repeated exposure to mostly vegetables with some findings on repeated exposure to fruits. Conclusion: This review advances the understanding of early food experiences and the development of food acceptability. Additional research is needed using diverse foods and textures with a focus on the transition to table foods.